Assessing the efficacy and safety of Juan Bi Tang for dialysis-related myofascial pain in the fistula arm: Study protocol for a randomized cross-over trial - Hsu, Yung-Tang; Ng, Hwee-Yeong; Chen, Yung-Hsiang; Huang, Yu-Chuen; Lee, Yan-Yuh; Tsai, Ming-Yen (Frontiers in Public Health, 2022)
Background Dialysis-related myofascial pain in hemodialysis (HD) patients is an important issue that is associated with many other psychosomatic problems. Effective interventions are required to alleviate pain in this group. Chinese herbal medicine (CHM) may be a potential therapeutic treatment for reducing pain. The aim of this study is to evaluate the effects of a classic CHM formula intervention on pain intensity, daily function, quality of life (QOL), and safety in patients receiving HD in a dialysis center within the context of southern Taiwan. Methods This will be a randomized, open label, cross-over trial with two parallel groups in a pre- and post-test study. Forty patients reporting myofascial pain related to the arteriovenous (AV) fistula in the arm during regular HD sessions will be recruited. Participants will receive 4 weeks of treatment with Juan Bi Tang (JBT) and 4 weeks of no treatment in a random order, separated by a washout period of 2 weeks. Treatment doses (3 g JBT) will be consumed thrice daily. The primary outcome measure will be the Kidney Disease Quality of Life 36-Item Short-Form Survey. Secondary outcomes will include the Fugl-Meyer Assessment-arm, Visual Analogue Scale (VAS) of pain, and grip strength. Outcomes will be collected before and after each intervention, for a total of four times per participant. The safety evaluation will focus on adverse events (AEs). Discussion This study will be the first to use CHM to treat patients receiving HD with dialysis-related myofascial pain in their fistula arm and to perform a complete assessment of the treatment, including records of QOL, arm function and muscle power, severity of pain, and safety. The results of the study will provide convincing evidence on the use of JBT as an adjuvant treatment for dialysis-related myofascial pain. Trial registration Clinicaltrials.gov registry (NCT04417101) registered 30 May 2020.